EXPLORING THE ROLE OF HOMEOPATHY IN RHEUMATOID ARTHRITIS: MECHANISMS AND CLINICAL EVIDENCE - Sharma, Leena (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Rheumatoid arthritis (RA) is a chronic, multisystem autoimmune disorder characterized by inflammation of the synovial joints, leading to pain, swelling, stiffness, and progressive joint damage. Conventional treatments, including nonsteroidal anti-inflammatory drugs (NSAIDs), disease-modifying antirheumatic drugs (DMARDs), and biologics, are effective but often associated with adverse effects such as gastrointestinal bleeding, hepatotoxicity, and increased infection risk. In this context, homeopathy has emerged as a complementary and alternative medicine (CAM) approach for managing RA. This review explores the mechanisms of action of homeopathic drugs in RA, focusing on immunomodulation, anti-inflammatory effects, and cytokine regulation. Preclinical studies demonstrate that remedies like Arnica montana, Ruta graveolens ,and Guaiacum officinale exhibit significant anti-inflammatory and antioxidant properties by modulating immune cells, reducing pro-inflammatory cytokines, and mitigating oxidative stress. Clinical evidence, though limited, suggests potential benefits of homeopathic drugs in improving symptoms, reducing inflammation, and enhancing quality of life. While these findings highlight the therapeutic potential of homeopathy in RA, further large-scale, randomized controlled trials are needed to validate its efficacy and establish its role as a complementary treatment.